Comparison of combinations of vectors to define the plane of the hand in order to calculate the attack angle during the sculling motion - Gomes, L. E.; Melo, M. O.; La Torre, M.; Loss, J. F. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Studies into swimming propulsion describe different combinations of vectors (different methods) to define the hand plane, which may alter the attack angle. The purposes of this study, which involved synchronized swimmers and swimmers in a real situation, were (i) to verify the agreement between the attack angles calculated using different methods, described in the literature and proposed by this study, to define the plane of the hand and (ii) to verify the variation in vector length of the methods found to be agreement in order to establish which method is most recommended when estimating the attack angle during sculling motion. METHODS: The sample consisted of 16 female participants (10 synchronized swimmers and 6 swimmers, all familiar with sculling actions). They performed sculling motion in a stationary vertical position (head above the water surface and with the water at chin level). Three-dimensional kinematic data from underwater video analysis was used to calculate the attack angle using different methods described in the literature, such as Schleihauf (1979), Berger et al. (1995) and Lauder et al. (2001) (Lauder 1-5), and a new combination (NC) proposed by this study to define the plane of hand. The degree of agreement was established between the attack angles calculated using different methods and the variation was verified in vector lengths of the methods that were found to be in agreement. RESULTS: The attack angles calculated from Schleihauf, Lauder 1 and NC methods were in agreement. The variation in length of two vectors of these methods was 12% and 17.9% for Schleihauf, 7.2% and 17.9% for Lauder 1 and 7.8% and 8.4% for NC. DISCUSSION: While Schleihauf, Lauder 1 and NC methods are in agreement, the vectors used in the NC presented a smaller variation in their lengths. We suggest using the NC method to calculate the attack angle when analyzing the sculling motion, as these results were obtained in a real situation as opposed to a model.